Phytosociological census of weeds in the sunflower crop - Brighenti, Alexandre Magno; Castro, Cesar de; Gazziero, Dionísio Luiz Pisa; Adegas, Fernando Storniolo; Voll, Elemar (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to survey the weeds in the preharvest of the sunflower crop in growers field of the southwest regions of Goiás State (Chapadão do Céu, Jataí and Montividiu) and Chapadão do Sul, Mato Grosso do Sul State, Brazil. Fifty one farms were evaluated, during the period of May to June, 2002, in a total of 583 m2 of area. The weeds were identified and counted inside a square (1.0x1.0 m), applied in each area, in order to determine the frequency, density, abundance and relative importance. Volunteer soybean (Glycine max) and corn (Zea mays) are part of the weed species in sunflower crop in the area. The botanical families Poaceae, Asteraceae and Euphorbiaceae present larger number of species. The main weeds found in the area are, in decreasing order, Ageratum conyzoides, Chamaesyce hirta, Cenchrus echinatus, Bidens sp., Euphorbia heterophylla and Commelina benghalensis.